Síntese de BiVO4 dopados com RuO2 aplicados na degradação eletroquímica - Francisco, Juliana Lucca (Universidade Federal de São Carlos, 2025)
The release of recalcitrant compounds from industries, hospitals, and agriculture into water bodies is considered a major global challenge, as these substances cause significant damage to the ecosystem. Based on this scenario, advanced electrochemical oxidative processes (AEPs) were analyzed as an alternative for pollutant mineralization. AEPs are based on the electrogeneration of oxidizing species, and the choice of material is crucial, as different species will be formed depending on the substance and the process. Therefore, the proposed work aimed to study and compare the anodic properties in chlorine of a promising and inexpensive n-type semiconductor, bismuth vanadate (BiVO4), and the same material doped with 1% ruthenium (Ru), which has excellent electrocatalytic properties. Therefore, through electrochemical and physical characterizations, the response of the doped material was analyzed to degrade two widely used antibiotics, sulfadiazine and sulfamethoxazole. The project began with the synthesis of pure and doped BiVO4 through electrodeposition of a bismuth(III) nitrate solution in ethylene glycol and the addition of a vanadyl acetylacetonate solution in dimethyl sulfoxide, followed by calcination and removal of excess vanadium. It is worth noting that the synthesis of the doped material follows the same procedure, the only difference being the addition of 1 mM ruthenium chloride to the bismuth solution. The materials produced were characterized physically and electrochemically. X-ray diffractometry confirmed the formation of monoclinic BiVO4, and its homogeneous morphology was observed by scanning electron microscopy. The doped material presented some agglomerates in its structure, possibly indicating greater film roughness, which would promote increased contact surface area. It also has a monoclinic structure, similar to the material without the addition of Ru. Furthermore, linear sweep voltammetry of the materials was analyzed over a range of -0.7 to 1.5 V vs. Ag/AgCl/KClsat, and the open-circuit potential was obtained for impedance analysis in sodium chloride solutions. Finally, the degradation of the selected pollutants was performed under optimized conditions, i.e., using the best material and potential considering the compounds typically observed in real effluents, accounting for the time required for complete decomposition of the compound.
Synthesis of RuO2-doped BiVO4 applied in electrochemical degradation
Keywords: Compostos recalcitrantes; Processos eletroquímicos oxidativos avançados; Vanadato de bismuto; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; 6. Água Potável e Saneamento